DIGITAL FATIGUE IN THE AGE OF SCREENS: EYE AND POSTURAL STRAIN AMONG 18–35-YEAR-OLD SCREEN USERS - Bagaji, Swizel; Rao, Roopa (International Journal of Research -GRANTHAALAYAH, 2025)
The pervasive use of digital devices has led to a sharp rise in screen-related health concerns, particularly among young adults. This study investigates the growing phenomenon of Computer Vision Syndrome (CVS) and associated postural strain among individuals aged 18–35 years, who are heavily reliant on screens for work, communication, and entertainment. With symptoms ranging from dry eyes, blurred vision, and headaches to neck and shoulder pain, digital fatigue poses a multifaceted risk to long-term well-being and productivity. An exploratory research targeting 160 participants was conducted employing a structured questionnaire, postural assessments via the Ovako Working Posture Analysis System (OWAS). Results revealed that 78.7% experienced symptoms of eye strain, including dryness, burning sensation, and blurred vision. 68.1% reported headaches or discomfort during or after screen usage. Musculoskeletal issues such as neck stiffness (59.4%) and shoulder discomfort (55%) were also prevalent. OWAS analysis confirmed that the majority of users exhibited moderate to high-risk postures, particularly while using mobile devices or laptops without ergonomic adjustments. Awareness of digital hygiene practices, such as the 20-20-20 rule or screen time breaks, was low among respondents. The findings highlight the growing health burden posed by digital fatigue among young screen users, exacerbated by lifestyle habits, poor ergonomics, and limited awareness. The study calls for urgent interventions in the form of structured awareness programs, digital wellness education, and workplace or academic ergonomics audits. Promoting preventive behaviour, proper posture, and regular eye care can significantly reduce the risk of long-term visual and musculoskeletal complications.